Thermoelectric properties of N-type Bi2Te2.7Se0.3 and P-type Bi0.5Sb1.5Te3 films for micro-cooler applications - Peng, Qi Zhen (2013)
Bi2Te3 and its solid solution remain the state-of-the-art thermoelectric materials for refrigeration applications in microelectronics industry, such as dissipating the heat generated by various devices. The fabrication method and associated processing parameters are to be optimised to get desirable composition exhibiting better electrical and thermal transport properties. Carrier concentration and mobility are found to be crucial in achieving high thermoelectric cooling efficiency and energy conversion. In this paper, we present the fabrication and analysis of thermoelectric thin films deposited by RF-magnetron sputtering from n-type Bi2Te2.7Se0.3 and p-type Bi0.5Sb1.5Te3 targets on a silicon substrate. X-ray diffraction, Scanning electron microscopy combined with energy dispersive spectrometry, electrical resistivity, Seebeck coefficient and thermal diffusivity measurements were used for the thermoelectric thin films characterization. We studied the effect of sputtering process parameters, on the structural, electrical and thermal transport characteristics of films. The observed results demonstrate both n-and p-type doped Bi2Te3 films exhibit desirable properties and could be potential candidates for thermoelectric micro-cooler applications.